Новая методика экспериментального исследования внутренней динамики цилиндрических зубчатых колес - Кириченко, А. Ф.; Федченко, Анна Валерьевна (НТУ "ХПИ", 2006)
The new scheme of a reducer where opportunities discretely are stipulated to enter those either other parameters or errors of gearing is developed and, thus, to trace influence of their change on a level of fluctuation of cogwheels.
Keywords: зубчатая передача; зубчатые колеса; редуктор; буксы; мощность